A Development Of The Jaran Bodhag Arts Perfomance In The Panji Laras Studios Of Probolinggo City: Perkembangan Pertunjukan Kesenian Jaran Bodhag Sanggar Panji Laras Kota Probolinggo - Endriana, Endriana Fayza Pramestya; Juwariyah, Anik (Solah, 2025)
This study aims to examine the development of the Jaran Bodhag art of the Panji Laras Studio, Probolinggo City, which includes movement, properties, players, and music. Art is recognized as an Inheritance Culture, Not an Object, in Indonesia in 2014. Jaran Bodhag was inspired by the Jaran Kencak art form, which is usually performed at circumcision ceremonies. However, underprivileged communities often modify it by creating Jaran Bodhag as an alternative. This study uses qualitative research to explore how Sanggar Panji Laras packaged the Jaran Bodhag art form into a performance. The results of this study reveal that the Jaran Bodhag art performance at the Panji Laras Studio includes a variety of movements. The props used are very simple, allowing dancers to use them in Jaran Bodhag, and the music consists of various kinds, giving the Jaran Bodhag performance vibrant color. It is hoped that the results of this study will contribute to a better understanding of traditional art in Indonesia and provide suggestions for the preservation and development of Jaran Bodhag in the future. Keywords : Development, show, art Jaran Bodhag